Ihsan Achievement Oriented Leadership: An Antecedent in Improving Human Resource Performance - Ammy Apriany; Olivia Fachrunnisa (Budapest International Research and Critics University, 2022)
The success of a leader in a business organization is determined by the leader ability to guide and to inspire subordinates to be willing to contribute to organizational goals. In addition, in an organization where the majority of its members are Moslems, a suitable leader is a leader who has Islamic values or commonly known as ihsan achievement-oriented leadership (IAOL). From the IAOL leadership model, it can encourage employees to always be involved in ta’awun behavior which can eventually give impact on HR performance in a business organization. From leadership models that have been studied by researchers, only a few have explored the IAOL and ta’awun leadership models, as well as their outputs on HR performance. The objective of this study was to contribute to the development of research on the IAOL leadership model, ta’awun behavior and HR performance. This study examined the mediating role of ta’awun behavior on the influence of IAOL leadership on HR performance. Data were collected from employees who work in a construction service company with a total sample of 141 people, and this study used a quantitative research paradigm with Partial Least Square (PLS) analysis tools. The results of this study indicated that the factor that can improve the performance of human resources is the IAOL leadership model, and its influence can be mediated perfectly by ta’awun behavior. Concisely, ta’awun behavior is able to act as a mediating variable on the influence of IAOL leadership on HR performance.